Hope and grit: the driving forces behind student-athletes’ motivation in sports and academics - Longakit, Jet C.; Lobo, Joseph; Panganiban, Teejay; Sinag, Jay Mark D.; Celestial, Elvie F.; Ballera, Janice D. (International Journal of Evaluation and Research in Education (IJERE), 2025)
While the challenges student-athletes face in balancing academics and sports have garnered increasing attention, few studies have explored how factors like hope and grit contribute to this balance and enhance motivation. This study investigated the relationship between hope, grit, and motivation of academic and sports of student-athletes. A total of 247 student-athletes of Mindanao State University-Iligan Institute of Technology (MSU-IIT) answered a set of questionnaires assessing grit, dispositional hope, and student-athletes motivation towards sports and academics with the age range of 18-24 years old. Ethical approval was gained from the participants. The results showed that factors of hope (agency and pathways) and grit (consistency of interest or COI and perseverance of effort or POE) were significant predictors of motivation in sports and academics. This suggests that student-athletes with higher levels of hope and grit demonstrate increased motivation in both domains. These results could offer a more valuable insights for coaches, educators, and sports psychologist striving to support the long-term success and wellbeing of student-athletes.